Hubungan Intellegence Quetient (IQ) Terhadap Hasil Belajar Pada Siswa Sekolah Dasar - Ali, Damsir; Alvionita, Fani (Faculty Of Education, 2024)
The learning process that occurs in individuals is indeed something important, because through learning individuals get to know their environment and adapt to the environment around them. This is in accordance with Law of the Republic of Indonesia no. 20 of 2003 concerning the National Education System Article 1. This research design uses a quantitative design which can be interpreted as a research method based on the philosophy of positivism, used for research on certain populations or samples, sampling techniques are generally carried out randomly, data collection uses instruments research, quantitative/statistical data analysis with the aim of testing predetermined hypotheses. The population in this study was all 38 students of SD Pahlawan class IV. The sample used was 38 students of SD Pahlawan class IV. The sampling technique in this research was total sampling. The data analysis used in this research is univariate analysis and bivariate analysis. From the results of research using univariate analysis, it was found that the majority of the IQ of class IV students SD Pahlawan was at the genius level as many as 14 respondents (36.8%) and learning outcomes were at the poor level as many as 28 respondents (73.7%). Meanwhile, in the bivariate analysis, the results can be obtained that there is a relationship between Intelligence Quotient (IQ) and student learning outcomes at Elementary SD Pahlawan Island for the 2023/2024 school year.